Cross-age networks, successful aging, and depression among Middle-aged South Koreans living in Seoul. Issue 1 (2nd January 2021) - Kim, Minhye
ABSTRACT: This study examines cross-age networks among middle-aged Seoul citizens using a name-generator approach (50–64 years, n = 828). The proportion of middle-agers with cross-age networks was rather small. The likelihoods of having networks with younger or older generations were related to one's socioeconomic characteristics. The existence of networks with younger generations was significant on successful aging and depression, whereas the existence of networks with older generations was not. Among the respondents with one or more cross-age networks, having younger network members was related to a higher likelihood of the perception of successful aging and greater closeness was associated with lower depression score.